Preliminary evaluation of the friends for life program on students' and teachers' emotional states for a school in a low socio-economic status area - Iizuka, C.; Barrett, P.; Gillies, R.; Cook, C.; Marinovic, Welber (Social Science Press, 2015)
The purpose of this study was to examine the impact of the FRIENDS for Life program on students' and teachers' emotional outcomes in a school serving a high-poverty population. The focus of the intervention was to train/coach teachers with strategies to develop social and emotional skills for students. A single group, pre/post-test design was used to conduct a preliminary investigation of the intervention to improve participants' social and emotional outcomes. At the end of the intervention, students who were at risk showed significant decrease in their anxiety levels and teacher's demonstrated significant improvements on their emotional resilience.